PAVING STONE BERBAHAN ABU SAMPAH TANAMAN - Yusuf Wahyudi (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2007)
AbstractThis paper discusses about the advantage of organic disposal ashas an additive on paving stone mixture. The organic disposals such asleaves, wood stick, etc. were taken from garbage tank at the market,living area, and temporary tank. Then they were burnt in to an artificialfurnace at temperature of 28-500°C for about 195 minutes. The mixdesign were 1 portland cement: 3 sand: 3 stone ash: organic ash of0%, 10%, 11%, 12%, 13%, 14% and 15% of cement weight: 0,6 water.The result showed that organic disposal ash ratio was 0.05, and thegradation was observed in zone III. The weight of paving stonecontaining organic disposal ash was smaller than normally paving stone.The more organic disposal ash the lighter weight of paving stone. Thecompressive strength of paving stone containing 12% of plant ash wasthe strongest, it was 119% of the control.Key word: compressive strength, paving stone, organic disposal ash